FAKTOR-FAKTOR YANG MEMENGARUHI USIA MENIKAH PADA WANITA USIA SUBUR DI DESA PANCUR NAPITU KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN TAHUN 2017 - Oktafiana Manurung (Elisabeth Health Jurnal, 2017)
From the information of midwife coordinator in Pancur Napitu Village, Simalungun Regency, there are many married teenagers and interviews of 15 mothers who have given birth with <20 years of age. Goals : The purpose of this study is to analyze the factors that affect the age of marriage in women of childbearing age. Methods : Type of survey research with cross sectional approach. Population is all Women Age Fertile in Pancur Napitu Village Tanah Java Subdistrict Simalungun Regency as many as 371 people, 154 sample with simple random sampling technique. Data obtained through interview with questionnaire. Data were analyzed by univariate stage, bivariate using chi-square and multivariate test using multiple logistic regression analysis at significance level 95% Result : The results showed that respondents who married at age ≥ 20 years amounted to 68.8% and married at age <20 years of 31.2%. There is influence of education, socioeconomic, knowledge and virginity value to married age. The most influential variable is education with the value of coefficient B 10,196. The percentage correct score of 80.5% indicates educational, socioeconomic, knowledge, and virginity values can explain its effect on the age of marriage in women of childbearing age. While the rest of 19.5% influenced by other factors. Conclution : It is recommended to Pancur Napitu Puskesmas and Kepala Desa to cooperate with local government in counseling to increase knowledge about marriage age and to prevent problems of pregnancy complication that often occur in WUS. As well as increasing the family's economic income for high education children, good knowledge, and avoid free association through the addition of workload.